地球温暖化への再考 - 佐藤 典人 (法政大学文学部, 2004)
Today it is a matter of public interest as well as of concern that the temperature of the earth will warm up gradually. Also they say that the increasing temperature of our earth's temperature until 2100 will be estimated at several degrees centigrade or the rise of its temperature will occur typically in the high latitudes of the earth in comparison with the low latitudes(Fig.6,7 and 8). The researchers of environmental science have pointed out that the main cause of this phenomenon has been increasing the concentrations of atmospheric carbon dioxide (=CO2)during the last century because we discharged many polluted substances through our industrial activities,that is,the increasing of fossil fuel combustion. As the same time as these activities,we have been emitting other gases,fox example chrorofluoro carbons which have been well-known as the cause of the decreasing ozone layer over the Antarctic or the Arctic. As a result,the“green-house effect”means that the atmospheric CO2 can't reflect the short waves from the sun but can do the long waves from the earth,and finally the energy of radiation from the earth to the space will accumulate in the atmosphere. Will this situation continue endlessly? I think that the global warming isn't simple as people are thinking. If we review the very long history of this earth,we can remembere easily that the concentrations of atmospheric CO2 won't increase simply. When we think about the history of this earth,we can be also remeinded of the cycle of CO2 connecting with the ocean,the atmosphere and the biosphere(Fig.1). In this cycle it is a very important factor,that this CO2 is movable. Furthemore it is obvious that both the CO2 in the atmosphere and in the ocean compare to that in the biosphere are movable easily along that cycle. Though we can know that the volume of CO2 in the ocean is larger than other volumes of each substance,unfortunately we can't understand yet that the precise volume of CO2 in the ocean as well as the maximum limit of its content. But at least the ...